Invited review: Reliability computation from the animal model era to the single-step genomic model era - Ben Zaabza, Hafedh; Van Tassell, Curtis P.; Vandenplas, Jeremie; VanRaden, Paul; Liu, Zengting; Eding, Herwin; McKay, Stephanie; Haugaard, Katrine; Lidauer, Martin H.; Mäntysaari, Esa A.; Strandén, Ismo (American Dairy Science Association, 2023)
The calculation of exact reliabilities involving the inversion of mixed model equations poses a heavy computational challenge when the system of equations is large. This has prompted the development of different approximation methods. We give an overview of the various methods and computational approaches in calculating reliability from the era before the animal model to the era of single-step genomic models. The different methods are discussed in terms of modeling, development, and applicability in large dairy cattle populations. The paper also describes the problems faced in reliability computation. Many details dispersed throughout the literature are presented in this paper. It is clear that a universal solution applicable to every model and input data may not be possible, but we point out several efficient and accurate algorithms developed recently for a variety of very large genomic evaluations.
Keywords: reliability; dairy cattle; genomics; estimated breeding values; single-step genomic models; reliability computation